Plan de negocios para la creación de la empresa Soluciones Integrales SAS (2022)
This project will structure a business plan for the creation of the enterprise Soluciones Integrales SAS, which is an income-generating project whose main objective is to provide an engineering service for Network Operators (NO), advised by professionals in Control Engineering and Industrial Automation with experience in electrical infrastructure, medium and low voltage distribution networks and telecommunications, as well as remote management systems, which are supported in an operational front in Control Center, where through specialized supervision systems the entire electrical infrastructure is monitored. The methodology used to meet each of the objectives was the analysis and procedure for the formulation and evaluation of projects considering the implementation of various studies such as Business Concept, Market Analysis, Production and Quality, Organization and Management, Economic and Financial Feasibility Study and finally the Economic Evaluation, taking as a reference the booklet of the Chamber of Commerce of Bogota "Guide for the formulation and development of your Business Plan".